Tracking the history of cultural eutrophication in High Arctic waterbodies - Gallant, Lauren; Kimpe, Linda; Hargan, Kathryn; Blais, Jules (Anthropocene, 2020)
Human activities can greatly affect the chemical and biological composition of High Arctic lakes that otherwise receive only sparse inputs from their watersheds and airsheds. Here we present a study of three High Arctic waterbodies in which wastewater from an airport was released over the span of several decades. Using sediment cores from these waterbodies, we reconstructed the history of wastewater inputs using a multiproxy approach consisting of sterols, stanols, metals, and stable isotopes of carbon and nitrogen. This multi-proxy approach showed good concordance between 15N, coprostanol (a stanol specific to human fecal sources), cholesterol, and cholestanol, which tracked the known history of human wastewater deposition to this High Arctic environment. Concentrations of plant derived sterols, such as campesterol and sitosterol, increased at the time of wastewater input, presumably due to increased plant growth stimulated by wastewater nutrients. Metal(loid)s normalized to titanium showed copper and lead tracked the input of wastewater into R-12, while arsenic, cadmium, chromium, nickel, and zinc increased more than 15 years after the onset of wastewater input. These results demonstrated the ability of sterols and stanols to reconstruct the historical presence of humans in High Arctic locations within the last 80 years and provided compelling evidence that these paleolimnological approaches may be used to track occupation of Arctic peoples beyond the last century.